Magnetic susceptibility, composition, and morphology of iron oxide particles resulting from ball milling of natural sand in the Rokan River - Elfitah Ramadhani Triana; Salomo Salomo; Erwin Amiruddin; Rahmondia Nanda Setiadi (Indonesian Physics Communication, 2024)
The magnetic susceptibility value and alterations in the composition and dimensions of iron oxide particles in the natural sand from the Rokan River, which were prepared using ball milling (BM), have been measured. Prior to undergoing the BM procedure, the sample's magnetic and non-magnetic particles are initially separated using an iron sand separator and a neodymium iron boron magnet. Subsequently, a 120-gram sample was obtained and subjected to the initial stage of BM for a duration of 80 hours, resulting in the formation of a product referred to as BM1. Next, product BM1 undergoes a second stage of BM with an extended duration of 30, 40, and 50 hours. The resulting products are termed BM2A, BM2B, and BM2C, respectively. The milled balls utilised were a total of 16 combined iron balls with a diameter of 2 cm, 32 combined iron balls with a diameter of 1.5 cm, and 64 combined iron balls with a diameter of 0.7 cm. The findings indicated a positive correlation between the duration of BM rotation and the magnetic susceptibility value. Specifically, the value increased from 11,361.6 in BM1 to 12,398.7 in BM2A, 13,383.4 in BMB, and 14,541.2 in BM2C. The XRF test findings also indicated an increase in the fraction of the magnetic element, Fe, from 38.113% in BM1 to 40.133% in BMA, 41.629% in BM2B, and 42.478% in BM2C. The SEM test findings indicated a decrease in the average particle size of the samples from 696 nm to 401, 356, and 288 nm.